2003
DOI: 10.1007/s00234-003-1057-2
|View full text |Cite
|
Sign up to set email alerts
|

Gliomatosis cerebri evaluated by 18F?-methyl tyrosine positron-emission tomography

Abstract: Gliomatosis cerebri is a rare condition in which an infiltrative glial neoplasm spreads through the brain with preservation of the underlying structure. CT and MRI show diffuse abnormal density or signal, without mass effect, and because these findings are nonspecific, it is difficult to make a definitive diagnosis. Our purpose was to assess the usefulness of a new tumour-detecting amino acid tracer for positron-emission tomography (PET), L-[3-(18)F] alpha-methyl tyrosine (FMT), in patients with gliomatosis ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…FAMT is transported into cancer cell by L-type amino acid transporter 1 (LAT1) and showed high specificity for malignant tumors [9]. The clinical usefulness of FAMT-PET has been shown for the diagnosis of various types of malignant tumors such as brain tumor and lung cancer [9][10][11]. Previous studies showed the correlation of FAMT uptake with tumor proliferative activity evaluated by the Ki-67 immunostaining (Ki-67 labeling index, Ki-67 LI) as well as the prognosis of patients with non-small cell lung cancer (NSCLC) [9,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…FAMT is transported into cancer cell by L-type amino acid transporter 1 (LAT1) and showed high specificity for malignant tumors [9]. The clinical usefulness of FAMT-PET has been shown for the diagnosis of various types of malignant tumors such as brain tumor and lung cancer [9][10][11]. Previous studies showed the correlation of FAMT uptake with tumor proliferative activity evaluated by the Ki-67 immunostaining (Ki-67 labeling index, Ki-67 LI) as well as the prognosis of patients with non-small cell lung cancer (NSCLC) [9,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Shintani et al [36] demonstrated that serial PET may be used to evaluate the extent of GC. Sato et al [39] examined 8 patients who had GC and 6 patients who had nonneoplastic disease with L-18 F-α-methyl tyrosine (FMT) PET and FDG PET. They observed significant differences between the standardized uptake (SUV) of FMT and the tumor-to-normal cortex (T/N) ratio of FMT in GC and in the controls, and between the T/N ratio of FMT and FDG in GC.…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%
“…A few studies that describe PET fi ndings in GC using different tracers have been reported [36][37][38][39] . Dexter et al [38] using 2-18 F-2-deoxy-D-glucose (FDG) PET, demonstrated tumor-associated cortical suppression of glucose metabolism in areas of involvement in a single patient with GC.…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%
See 1 more Smart Citation
“…L2 L-3-[18F]-Fluoro-ot-methyltyrosine (FMT)-PET was developed in our institute and showed high specificity for several malignant tumors as compared with FDG-PET. [3][4][5] In the present study, we compared the diagnostic ability of FMT-PET and FDG-PET for the diagnosis of maxillofacial tumors.…”
Section: Although 2-[18f]-fluoro-2-deoxy-d-glucose (Fdg)-positron Emimentioning
confidence: 99%